1995
DOI: 10.1021/ja00113a011
|View full text |Cite
|
Sign up to set email alerts
|

Squarylium Dyes: Structural Factors Pertaining to the Negative Third-Order Nonlinear Optical Response

Abstract: Off-resonant electric field induced second harmonic generation (EFISH) and resonant third harmonic generation (THG) measurements of two squarylium dyes are reported. The magnitude of is large for both processes. The EFISH measurement clearly shows that the off-resonant third-order polarizability is negative, a consequence of the dominance of a non-two-photon mechanism. This unusual result is in agreement with our earlier reports on two other squarylium dyes. Resonant THG measurements strongly suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
117
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 0 publications
9
117
1
Order By: Relevance
“…The results are in qualitative agreement with previous data reported by Dirk et al who found ISQ4 to be slightly more stable than ISQ6. 31 The energy differences between the isomers are very likely due to the different number of intramolecular hydrogen…”
Section: Electronic Spectrum Of Isqmentioning
confidence: 99%
“…The results are in qualitative agreement with previous data reported by Dirk et al who found ISQ4 to be slightly more stable than ISQ6. 31 The energy differences between the isomers are very likely due to the different number of intramolecular hydrogen…”
Section: Electronic Spectrum Of Isqmentioning
confidence: 99%
“…Here, we present our initial results on the synthesis of a novel chiral squaraine dye [10] and the investigation of its unique aggregation behavior in aqueous solution and on a solid substrate. Condensation of electron-rich aromatics with squaric acid in an azeotropic solvent mixture such as toluene/1-butanol provides a simple access to squaraines.[11] Highly activated N,N-dialkylated 3,5-dihydroxyanilines are conveniently generated in situ by condensation of secondary amines with 1,3,5-trihydroxybenzene (phloroglucinol), [12] and subsequent reaction with squaric acid in the same pot leads to formation of bis(4-dialkylamino-2,6-dihydroxyphenyl)squaraines, which offer the advantages of much higher intrinsic fluorescence quantum yields, [1a] increased relative chemical stability, [7g,13] and stronger aggregation tendency [1b,7d,14] than their non-hydroxylated analogues. Such a two-step, one-pot procedure [12] can also be applied to the synthesis of polysquaraines, useful for cation sensing.…”
mentioning
confidence: 99%
“…Such a two-step, one-pot procedure [12] can also be applied to the synthesis of polysquaraines, useful for cation sensing. [15] Since secondary amines are mandatory to avoid squaramide formation, [11b] the natural amino acid L-proline is an obvious choice for a chiral building block.…”
mentioning
confidence: 99%
“…This in turn enabled us to choose appropriate parameters for the charged oxygen and nitrogen atoms because the core charges, ionization potentials, electron affinities, [12] and Slater exponents [17] for O ± and N + differ from those for O and N. [18] All-valence electron calculations (including MNDO [11] and CNDO/S (complete neglect of differential overlap/ spectroscopic parameters) [14] ) on squaraine dyes give excitation energies that are too high and Bigelow and Freund needed to introduce a substantial post-calculation correction factor. [11] Within the SCF-PPP-CI approximation, however, the use of a carefully selected set of parameters has been shown to give good agreement with experimental excitation energies.…”
Section: Calculation Of the First Hyperpolarizability Tensormentioning
confidence: 99%